2022
DOI: 10.3389/fphar.2022.1020556
|View full text |Cite
|
Sign up to set email alerts
|

Biological and therapeutic role of LSD1 in Alzheimer’s diseases

Abstract: Alzheimer’s disease (AD) is a common chronic neurodegenerative disease characterized by cognitive learning and memory impairments, however, current treatments only provide symptomatic relief. Lysine-specific demethylase 1 (LSD1), regulating the homeostasis of histone methylation, plays an important role in the pathogenesis of many neurodegenerative disorders. LSD1 functions in regulating gene expression via transcriptional repression or activation, and is involved in initiation and progression of AD. Pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…Poggi et al have reported that SOD1 can reduce the risk of RDS, IVH, and ROP in a study of 152 preterm infants ( 91 ). Regarding the involvement of other antioxidant genes, KDM1A that can regulate homeostasis of histone methylation ( 92 ) has been reported to play a role in regulating autophagy. It is involved in the transcriptional control of various downstream effectors ( 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…Poggi et al have reported that SOD1 can reduce the risk of RDS, IVH, and ROP in a study of 152 preterm infants ( 91 ). Regarding the involvement of other antioxidant genes, KDM1A that can regulate homeostasis of histone methylation ( 92 ) has been reported to play a role in regulating autophagy. It is involved in the transcriptional control of various downstream effectors ( 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…These data highlight the importance of LSD1; however, inhibition studies strongly suggest that inactivation provides benefit to CNS-related diseases (Li et al 2022b). Therefore, LSD1 inhibition is being targeted in CNS disease (Fang et al 2019;Antonijoan et al 2021;Li et al 2022b). The observed LSD1 paradox for the CNS likely reflects the impact of LSD1 on the cell of origin and the need for LSD1 protein versus enzyme activity.…”
Section: Histone Lysine Methylation Erasersmentioning
confidence: 99%
“…When overexpressed, LSD1 promoted a delay in neurodegeneration and gene expression alterations (Christopher et al 2017). These data highlight the importance of LSD1; however, inhibition studies strongly suggest that inactivation provides benefit to CNS-related diseases (Li et al 2022b). Therefore, LSD1 inhibition is being targeted in CNS disease (Fang et al 2019;Antonijoan et al 2021;Li et al 2022b).…”
Section: Histone Lysine Methylation Erasersmentioning
confidence: 99%
“…T-448, a LSD1-specific inhibitor, could restore the learning function in an NMDAR hypofunction mice model by elevating the H3K4 methylation levels in the brain . Deregulation of the LSD1 transcription modulation is also involved in the pathogenesis of Alzheimer’s disease (AD), and it has been evaluated as a therapeutic target in the treatment of AD . LSD1 inhibition by TAK-418, a structural derivative of T-448, could normalize aberrant gene expression in the brain of a valproic acid (VPA) rat model and a poly I:C mouse model of neurodevelopmental disorders .…”
Section: Lsd1: Mythbuster To a Therapeutic Targetmentioning
confidence: 99%
“…32 Deregulation of the LSD1 transcription modulation is also involved in the pathogenesis of Alzheimer's disease (AD), and it has been evaluated as a therapeutic target in the treatment of AD. 33 LSD1 inhibition by TAK-418, a structural derivative of T-448, could normalize aberrant gene expression in the brain of a valproic acid (VPA) rat model and a poly I:C mouse model of neurodevelopmental disorders. 34 The success in deciphering the therapeutic benefits of LSD1 inhibition prompted the exploration of the development of specific LSD1 inhibitors for various diseases.…”
Section: ■ Introductionmentioning
confidence: 99%